Penterjemahan Mahua sebagai Strategi Budaya: Kajian Kes Gerakan Sastera 31 Mei: Translating Mahua as a Cultural Strategy: A Case Study of the May 31 Literary Movement (KEMANUSIAAN The Asian Journal of Humanities, 2025)
This article examines the May 31 Literary Movement initiated in the 1980s by Mahua translators in collaboration with Dewan Bahasa dan Pustaka (DBP). The campaign was initiated to promote national unity through the translation of literary works and cultural performances. On 31st May 1983, DBP convened a meeting of writers from various ethnic backgrounds which resulted in the formation of Coordinating Committee for the Translation of Multiracial Writers and then launched a series of cultural performances and literary translation initiatives. One of the pioneers of this movement, Usman Awang stated that “May 13 represents prejudice and division, while May 31 is a day for promoting interaction through translation, mutual understanding and unity”. Although the movement was small in scale and had limited influence on Mahua literature, it remains a significant milestone in Malaysian literary translation history, marking the first structured collaboration between DBP and the Chinese community on cultural matters. This article situates the movement within a broader historical context, tracing the formation of Chinese bilingual intellectuals since independence and examining how the May 13 Incident shaped their translation practices and identity formation in the evolving post-tragedy political landscape. The finding of this article shows that translation has been employed as a cultural strategy by the Chinese community in their pursuit of the ideal of multiculturalism.